The Logic of Logistics Theory, Algorithms, and Applications for Logistics Management - Simchi-Levi, David; Chen, Xin; Bramel, Julien (Springer Series in Operations Research and Financial Engineering, 2014)
Fierce competition in today's global market provides a powerful motivation for developing ever more sophisticated logistics systems. This book, written for the logistics manager and researcher, presents a survey of the modern theory and application of logistics. The goal of the book is to present the state of the art in the science of logistics management. This third edition includes new chapters on the subjects of game theory, the power of process flexibility, supply chain competition and collaboration. Among the other materials new to the edition are sections on discrete convex analysis and its applications to stochastic inventory models, as well as extended discussions of integrated inventory and pricing models. The material presents a timely and authoritative survey of the field that will make an invaluable companion to the work of many researchers and practitioners.   Review of earlier edition:   "The present book focuses on the application of operational research and mathematical modelling techniques to logistics and supply chain management (SCM) problems. The authors performed a substantial revision of the 1st edition and included a number of new subjects ... . The book is carefully written and is an important reference for readers with a solid background in probability and optimisation theory ... . the present book should be seen as a valuable guide describing techniques that can be applied or adapted to real-life situations." (OR News, Issue 25, 2005).